Determinación de la eficiencia de agentes demulsificantes según su familia química en la desestabilización de emulsiones de agua en crudo pesado (2017)
Petroleum industry has a great influence in Colombian economy. Because of this, the drastic price drop of a crude oil barrel in 2014 forced Colombian petroleum companies to improve their production process in order to be economically viable. 55% of Colombian crude oil reserves are heavy crude oil. Crude oil characterises for having water in oil emulsions. Breaking these emulations implies in high transport and refinery costs. The most common method to break these emulsions is to add a demulsifier agent in order to destabilize them. According to the above, this paper pretends to analyse different demulsifier agents in order to determine its efficiency according to its chemical family. To determine its efficiency an experimental test is done, called Bottle Test...